The intersection of melanoma survival and social determinants of health in the United States: A systematic reviewCapsule Summary - McKenzie E. Maloney, BS; Caleb Bacak, BS; Kellen Tjioe, DDS, MSc, PhD; Loretta S. Davis, MD; E. Andrew Balas, MD, PhD; Gagan Agrawal, MS, PhD; Jorge E. Cortes, MD; Marisol Miranda-Galvis, DDS, MS, PhD (Elsevier, 2024)
Background: Despite recent improvements in melanoma survival rates, persistent inequalities pose barriers to care for some patients. Objective: To assess the influence of social determinants of health (SDoH) on melanoma treatment outcomes. Methods: A systematic review (Prospective Register of Systematic Reviews CRD42022346854) of manuscripts that examined the association between SDoH and melanoma treatment-related outcomes in the United States was conducted using 5 databases. Results: The analysis encompassed data from 12 retrospective manuscripts. The SDoH domains most frequently investigated were health care access and quality (n = 6 manuscripts, 50%) and economic stability (n = 7, 58.3%). Other domains included social and community context (n = 5, 41.7%) and education access (n = 3, 25%). These findings revealed significant correlations between poor melanoma survival and low levels of economic stability, limited education, government health insurance, and being uninsured and unmarried. Limitations: Many SDoH were not analyzed at the patient level. SDoH are vast categories, but manuscripts usually analyze one aspect of a particular category. Conclusions: These results highlight the need for physicians to recognize the substantial impact of SDoH on melanoma outcomes and to adopt more comprehensive strategies focused on patient-centered care. Integrating social support mechanisms into clinical practice emerges as a key mechanism to promote equitable and effective interventions.